Hubungan Premenstrual Syndrome (PMS) Dengan Kualitas Tidur Mahasiswi Program Studi Keperawatan Program Sarjana Universitas Harapan Bangsa - Dini Ristya Lestari; Siti Haniyah; Ikit Netra Wirakhmi (Journal Innovation In Education, 2024)
Premenstrual Syndrome or what is often referred to as PMS is discomfort or physical and mental signs that appear when a woman approaches her menstrual period. One of the factors related to PMS is the quality of sleep, the severity of PMS symptoms will worsen the quality of a woman's sleep. The purpose of this study was to understand the relationship or correlation of Premenstrual Syndrome in Nursing Study Program students at the Harapan Bangsa University Undergraduate Program. The approach used in this study is a quantitative method with a cross-sectional research design. Sampling technique with a total sampling of 53 semester 6 students of the Nursing Study Program Undergraduate Program. This study used two questionnaires, namely (sPAF) and (PSQI). The analytical method used was univariate and bivariate analysis using the Spearman Rank test. The results of the analysis using the software show that there is a significant relationship between premenstrual syndrome and sleep quality with a value of ρ = 0.005 where the value of ρ <α = 0.05, with a correlation coefficient of 0.382 which means there is a relationship between premenstrual syndrome and sleep quality with low correlation strength and the direction of the relationship positive.